The sacred and secular canon in romanticism preserving the sacred truths - Jasper, David (Macmillan [u.a.], 1999)
This book focuses on some of the greatest writers and artists of European Romanticism, including S. T. Coleridge, Wordsworth, J. M. W. Turner, Goethe, Holderlin and, in the later nineteenth century, Matthew Arnold. Concluding with a discussion of the significance of Romanticism for our understanding of postmodernity, its various chapters explore the place of the biblical canon as the central element in the shift from the sacred to the secular, and the place of the Bible in the development of our concept of Weltliteratur, or world literature, as definitive of culture. This book will be of interest to all concerned with art, literature and the development of biblical criticism and religious thought.
Keywords: Bibel; Geschichte 1800-1900; Geschichte 1798-1832; Duits; Engels; Godsdienst; Het heilige; Letterkunde; Romantiek; Deutsch; Englisch; Geschichte; Literatur; Religion; English literature -- 19th century -- History and criticism; German literature -- 19th century -- History and criticism; Holy, The, in literature; Religion and literature -- History -- 19th century; Romanticism in art; Romanticism -- Germany; Romanticism -- Great Britain; Romantik; Deutschland; Großbritannien